LEXICAL DENSITY AND GRAMMATICAL INTRICACY OF READING MATERIALS IN ENGLISH IN FOCUS TEXTBOOK FOR FIRST GRADE OF JUNIOR HIGH SCHOOL - Amna Apriany Delima Batubara and Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study aims to find out the lexical density and grammatical intricacy of English reading texts in the textbook for the 1st grade of junior hih school to measure the difficulty of the text. The objectives of the study are to find out the lexical density and grammtical intricacy which formed in the reading texts of English in Focus Textbookwhich has the highest both of lexical density and grammatical intricacy. This study was conducted by descriptive method with qualitative research. The data of this research were the English reading texts of English in Focus Textbook for First Junior High School. The data were text analyzed by using Halliday’s theory. The result of this study; 1).Lexical density formed of the texts was high based on Halliday’s theory that the texts had more lexical item than grammatical item, Text 1 was 57.31%, Text 2 was 70.83%, Text 3 was 68.75%, Text 4 was 61.36%, Text 5 was 58.82%, Text 6 was 60.86%, Text 7 was 69.23%, Text 8 was 71.42%. Grammatical Intricacy formed of the texts was high based on Halliday’s theory that the texts had more complex clauses than simple clause, Text 1 was 7, Text 2 was 4, Text 3 was 2.16, Text 4 was 2, Text 5 was 1.08, Text 6 was 1.75, Text 7 was 2, Text 8 was 2. 2).Lexical density influences the difficulty of reading texts if it has higher proportion of lexical items than grammatical items. While grammaticcal intricacy also influences the difficulty of reading texts if it has higher proportion of complex clauses in comparison with simple clauses. 3).The length of the sentence did not influence the grammatical intricacy of the texts but the more complex clauses and content carrying lexical items could make the reader difficult to process the texts.